2018
DOI: 10.1371/journal.pone.0201616
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hypertension in an agricultural village in Madagascar

Abstract: Elevated blood pressure presents a global health threat, with rates of hypertension increasing in low and middle-income countries. Lifestyle changes may be an important driver of these increases in blood pressure. Hypertension is particularly prevalent in African countries, though the majority of studies have focused on mainland Africa. We collected demographic and health data from 513 adults living in a community in rural Madagascar. We used generalized linear mixed models to assess body mass index (BMI), age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
(74 reference statements)
1
14
1
Order By: Relevance
“…The prevalence rates of hypertension found in this study were much higher than those (15.9%) recently reported for four states (Khartoum, Gezira, Blue Nile, and Kassala) in Sudan [15]. Interestingly, a much higher prevalence (49.1%) of hypertension was reported among 513 adults in a rural setting in Madagascar [12]. Conversely, a lower rate (28.0%) of hypertension was reported in Tanzania [13] and in a population-based sectional study that enrolled 67,397 participants in Ethiopia (31.9%) [24].…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…The prevalence rates of hypertension found in this study were much higher than those (15.9%) recently reported for four states (Khartoum, Gezira, Blue Nile, and Kassala) in Sudan [15]. Interestingly, a much higher prevalence (49.1%) of hypertension was reported among 513 adults in a rural setting in Madagascar [12]. Conversely, a lower rate (28.0%) of hypertension was reported in Tanzania [13] and in a population-based sectional study that enrolled 67,397 participants in Ethiopia (31.9%) [24].…”
Section: Discussioncontrasting
confidence: 84%
“…Because of our study design (controlled for age), it might not be valid to compare our results (age and hypertension) with the results of the large study that was recently conducted in four states (Khartoum, Gezira, Blue Nile and Kassala) in Sudan [15]. Several studies have shown that an older age is significantly associated with hypertension in neighbouring countries, including Ethiopia [8,9,11], Tanzania [13] and Madagascar [12]. Similarly, a recent metaanalysis including 43,025 older adults (> 53 years) in 15 African countries showed that an older age is independently associated with hypertension [25].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations